COMMERCE INFORMATION SYSTEM: VERAL VEHICLE RENTAL WEBSITE (VEHICLE RENTAL) WITH AGILE METHOD - M. Miftach Fakhri; Andika Isma; Muhammad Alif Leo; Arya Putra Abshari; Della Fadhilatunisa; Andi Naila Quin Azisah Alisyahbana (Jurusan Pendidikan Teknik Elektro, 2024)
The aim of this study is to develop a vehicle rental information system that facilitates users in borrowing vehicles. The research population consists of 27 students in Makassar, and data was collected through an online questionnaire. The system was tested using the Blackbox Testing method to assess its functions and features. The research findings indicate that Vehicle Rental (VeRal) can be utilized as an effective platform for borrowing vehicles. With VeRal, users can easily book vehicles according to their needs. The success of this system has the potential to enhance efficiency and convenience in vehicle rentals. This research contributes to the relevant field of study in the current digital era, where technology brings significant changes to various aspects of human life, including transportation.